Evaluate the renal system damage caused by zoledronic acid: a comprehensive analysis of adverse events from FAERS - Zhaojun Wang; Xin Su; Donglei Shi; Li Wei (BMC Cancer)
Abstract Background Zoledronic acid (ZA) is widely used for the treatment of osteolytic bone metastases in malignancies and osteoporosis, but it has been associated with renal impairment. In this study, we investigated adverse events (AEs) related to renal and urinary system diseases associated with ZA using the U. S. FDA’s Adverse Event Reporting System. Methods We collected FAERS data from Q1 2004 to Q1 2024 and used the reporting odds ratio to detect AEs related to renal and urinary system diseases associated with ZA. Additionally, we applied multiple algorithms, including ROR, proportional reporting ratio, bayesian confidence propagation neural network, and multi-item gamma poisson shrinker, to quantify renal and urinary AEs under different indications. Results A total of 52,495 AE reports involving ZA as the primary suspect drug were identified. Among renal and urinary system diseases, 25 distinct AEs were recognized, with renal tubular necrosis being the most frequently reported. For different indications, renal tubular necrosis was the most reported AE in breast cancer and osteoporosis; nephrogenic diabetes insipidus was both the most frequent and strongest signal in lung cancer; proteinuria was most common in multiple myeloma, and polyuria in prostate cancer. Furthermore, most AEs occurred in patients who had been on ZA for more than 360 days, followed by those within the first 30 days of use. Conclusion Based on pharmacovigilance data from FAERS, different renal and urinary system AEs should be closely monitored and addressed according to the specific indications for which ZA is used.